Notes on Stenhelmoides and description of the true male genitalia of S. strictifrons Grouvelle, 1908 (Coleoptera: Elmidae) - FERNANDES,André S. (2020)
ABSTRACT The genus Stenhelmoides comprises 15 species spread over all Central and South America and its greatest species richness is clearly associated with Amazonian regions. Based on examination of type specimens and additional material, we describe and illustrate the true male genitalia of Stenhelmoides strictifrons, which had until now been incorrectly illustrated in the literature. We also report new records of the genus Stenhelmoides from Brazil and Guyana. In addition to pictures of the species’ habitus, we provide pictures of the type specimens of Stenhelmoides grandis, S. grouvellei, S. guyanensis; S. strictifrons and S. submaculus. Based on the International Code of Zoological Nomenclature, we recognize additional paralectotypes for S. guyanensis and for S. grouvellei.